Students' Perception and Motivation In Learning English Towards The Use of Quizizz For Efl Students - Nur Amalia Solikhah; Cindyra Galuhwardani (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This research aimed to discover the students’ perception and motivation in learning English towards the use of quizizz features for EFL students. The method used in this research was a descriptive qualitative approach. Participants of this research were the students of Bina Sarana Informatika University, and the subject of this research was 42 students of 12.1A.21 class 2022/ 2023. Data collection techniques used were the questionnaire and interview results. Data analysis techniques used were basic statistical techniques of percentages using the Likert-scale questionnaire, and the data was supported from the interview’s results as the secondary data. The results of this research indicated intrinsic and extrinsic factors that influence students to participate in the learning English towards the use of quizizz features which include: 1) Intrinsic factors (challenging, curiosity, learning new things, improving their knowledge and English skill), 2) Extrinsic factors (getting a good mark, gaining good Grade Point Average, and getting experience of using quizizz features). It showed that the EFL Students have a good perception and good motivation in learning English towards the use of quizizz features for EFL students. In conclusion, learning English towards the use of quizizz features for EFL students is good, and this quizizz features can be considered as English learning and practice media, which will be better to combine with the conventional ways in the classroom.